Monitoring of nitrogen oxides at Svalbard: measurements in Adventdalen - Dekhtyareva, Alena (DataverseNO, 2018)
Main snowmobile route to the east coast of Spitzbergen from the Longyearbyen goes along the road through the valley Adventdalen, and therefore there is daily snowmobile traffic in spring season lasting from the end of March to the beginning of May. The chemiluminescence NO/NO2/NOx Analyzer (model T200) was installed in the UNIS CO2 lab in Adventdalen for the period from 23.03.2017 to 15.05.2017. The sensor was calibrated against span and null concentrations weekly, and the data was scaled to avoid zero drift. Current dataset represents concentration of NO, NO2 and NOx in the air during the spring snowmobile season at Svalbard. One can compare the concentration with other remote places in the Arctic during night-time with low snowmobile traffic. The influence of emissions from snowmobiles on the background concentration of NOx in Adventdalen has been studied together with the meteorological data from Adventdalen.